Mitigation of Ammonia Inhibition by Internal Dilution in High-Rate Anaerobic Digestion of Food Waste Leachate and Evidences of Microbial Community Response - Yun, Yeo-Myeong; Kim, Dong-Hoon; Cho, Si-Kyung; Shin, Hang-Sik; Jung, Kyung-Won; Kim, Hyun-Woo (WILEY, 2016)
A high-rate anaerobic digestion of food waste leachate were tested using intermittent continuously stirred tank reactors (iCSTRs) to evaluate how severe ammonia inhibition could be mitigated with internal dilution strategy, and to identify how bacterial and archaeal community respond in genus and species level. Experimental results show that the digestion performance was well maintained up to hydraulic retention time (HRT) of 40 days but could not keep steady-state as HRT decreased to 30 days due to severe free ammonia (FA) inhibition. Coupling internal dilution was the key to relieve the inhibition since it reduced FA concentration as low as 62 mg/L even at HRT 30 days, which corresponds to organic loading rate of 5 g COD/L/d, demonstrating CH4 yield of 0.32 L CH4/g CODadded. It was confirmed that the dilution offers iCTSRs manage severe ammonia inhibition with the balanced community structure between bacteria and archaea in this high-rate anaerobic digestion. Genus and species level pyrosequencing evidence that FA inhibition to community dynamics of Methanosarcina and Methanosaeta is strongly connected to methanogenesis, and Methanosarcina plays a key role in an iCSTR with the dilution. (C) 2016 Wiley Periodicals, Inc.
Keywords: SP-NOV; CATTLE MANURE; RIBOSOMAL-RNA; COMB-NOV; NITROGEN; METHANOSAETA; BIOREACTORS; BIOMETHANATION; ENVIRONMENTS; PERFORMANCE